The Dilemmas of Geographical Enlargement from the Perspective of an EU Candidate Country – The Republic of Serbia - Rakić, Branko M. (Maastricht 30: A Central European Perspective, 2025)
Starting from the autumn of 2000, Serbia’s central foreign policy objective has been membership in the European Union. For a long time, the enthusiasm of politicians (especially those in power) was shared by the majority of citizens. Nevertheless, the constant addition of new conditions (which was not the case with other countries seeking entry), some of which are unacceptable for both the political elite and the citizens of Serbia, and then the open announcements by some of the leading European politicians about the halt of EU enlargement for the foreseeable future, have led to significant decrease in the interest of Serbian citizens in EU membership. EU membership is still the number one foreign policy objective of the Serbian state, but in the absence of a clear, fast and certain European perspective, Serbia is increasinglythinking about finding alternatives. In practice, alternative solutions are being resorted to, even if temporarily. Even though the geographical position of Serbia and the depth of its economic and other relations with the EU and its member states so far make it necessary that each of these alternative solutions imply close relations between Serbia and the EU, but the absence of an unequivocal European perspective imposes the need to turn to other global partners, such as China, the USA, Russia or other countries. This positioning is in accordance with the historical experience of Serbia, which is traditionally involved cooperation with both East and West, and a balancing act between the two. In addition, it is possible and probable that this orientation towards other global actors and partners is fully in line with the changes currently taking place in the world and, above all, with the process of globalisation, by which the European Union itself is influenced and to which it will have to adapt. Keywords: accession, perspective, enthusiasm, disappointment, alternative, balancing, globalization.